PREVENTION OF THE SPREAD OF THE COVID-19 PANDEMIC IN THE TOURISM INDUSTRY IN PADANG PARIAMAN REGENCY - Nofriya Nofriya; Putri Nilam Sari (Faculty of Public Health, Andalas University, 2020)
The COVID-19 pandemic has drastically reduced tourism activities and has a significant impact on the economy. With the new normal concept, the government has re-opened tourism activities by implementing strict health protocols. This policy is also enforced in Padang Pariaman Regency. However, it is necessary to have clear guidelines for each type of industry related to tourism because the potential for transmission is different depending on the activities carried out. This study aims to examine the handling and prevention of the spread of the COVID-19 pandemic in the tourism sector, especially in Padang Pariaman Regency. The results show that there are regulations from the government regarding the application of health protocols in tourism activities. However, there is no direct control in its implementation, so that still possible for potential transmission of COVID-19. With the New Habit Adaptation regulation, it is expected to all people, especially tourism actors, understand and apply better health protocols to reduce the potential for COVID-19 transmission in the tourism sector.Â